Comparison between horizontal and vertical axis wind turbine - Mohammad A. Al-Rawajfeh; Mohamed R. Gomaa (International Journal of Applied Power Engineering (IJAPE), 2023)
Since ancient times, wind energy has been exploited in various fields, it was at the beginning used to rotate pumps for the purposes of agriculture and irrigation. At the beginning of the 18th century, wind turbines began to produce electricity with modest capacities. In the following years, the capacities of the turbines increased and it became necessary to deal with this increase by reducing losses and inventing new designs for turbines Suitable for working conditions and installation location. The rotor power coefficient in a wind turbine can reach 0.59 which is called the bets limit.  The vertical axis wind turbine (VAWT) design was invented for working conditions, capacities, and places, in which it may be difficult to install older Horizontal axis wind turbines (HAWT). The efficiency of the HAWT is still higher than the VAWT, in addition, the amount of efficiency in the HAWT is greater than the VAWT by 25% but the VAWT has the amount of torque more than the HAWT. The main objective of this research is to compare the VAWT and the HAWT, taking into account several aspects which have been reviewed to try to understand the importance of the two designs.